Socio economic condition of Black Bengal goat farmers and their goat management in rural areas of North Bengal region, Bangladesh - Shoshe, Nusrat Zahan; Islam, Md Tariqul; Mahmud, Md Abdullah Al (Research in Agriculture Livestock and Fisheries, 2019)
A study was conducted on 300 farmers of five districts in north Bengal region, Bangladesh to know the socio economic status of farmers and their goat management system. We have found that 82% farmers are Muslim and 70% females are involved with goat farming. Survey showed that 47% goat farmer’s age range is (15-30 year) and 68% (46% female and 22% male) farmers are in primary standard level. Landless or small marginal farmers are involved with goat farming (37%). This study reflects that 54% farmer’s annual income is within 10,000 Tk whether 37% goat farmers earn between (10,000-20,000 Tk) per year. Only 9% farmers earn more than 20,000 Tk per year. 100% farmers in rural area rear their goat by semi intensive system; 82% and 18% farmers use kacha and paka floor respectively. 86% farmers supply concentrates feed with green grass whereas only 14% farmers do not supply any concentrate feed to their goat. Farmers supplied 2.63±0.05kg/day green grass, 60.00±5.86g/day concentrate and 0.62±0.03kg/day tree leaves per animal during lactation stage. Maximum (61%) farmers have more than 10 goat and 25% have 5-10 no. of goat. The body wt of buckling, doeling, buck and doe were 6.12± 0.04kg, 5.92± 0.06 kg, 8.45±0.10 kg and 7.44±0.04 kg respectively. Most of the farmers (84%) use natural and few farmers (16%) use artificial insemination to their doe. The incidence of pneumonia (61%), fever (43%), diarrhoea (42%) and anorexia (60%) are high in up to 1 month of age. Incidence of goat pox (58%) and alopecia (54%) are high in the age of above 9 months and ectoparasitic infestations (51%) are high in the age of (1-9) months. From above discussions we can concluded that Socio economic condition of farmers in rural area of North Bengal region is not so good. To enhance the production potential of the breed it is essential to introduce superior technologies and to create necessary facilities of improved practices in goat keeping. Res. Agric., Livest. Fish.6(1): 111-118, April 2019